1995
DOI: 10.1177/095632029500600405
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Targeting of anti-HIV Nucleosides: Distribution of 3′-azido-3′-deoxythymidine (AZT) and 3′-azido-2′,3′-dideoxyuridine (AZdU) after Administration of Dipalmitoylphosphatidyl Prodrugs to Mice

Abstract: SummaryHuman immunodeficiency virus appears to be proliferating within the lymphatic system throughout the period of clinical latency. Targeting of anti-HIV compounds to the lymphatic tissue may therefore provide therapeutic benefits. The purpose of this investigation was to determine the distribution of 3'-azido-3'-deoxythymidine (AZT) and 3'-azido-2',3'-dideoxyuridine (AZdU) in lymph nodes in a mouse model after administration of the lipophilic prodrugs dipalmitoylphosphatidyl-azidodeoxythymidine (DPP-AZT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This discovery suggested that targeting of AIDS drug to lymphatic tissue and sustaining a high therapeutic drug concentration in lymphatic tissue may improve therapeutic benefits, especially in the latent period. However, it has been reported that azidothymidine (AZT) administration during an early clinical latent stage did not provide benefits to HIV -infected patients, 3 since AZT fails to be targeted and sustained in lymphatic tissue, 4 • 5 and has serious side effects and drug resistance. 6 Therefore, preparation of an AZT prodrug which may deliver AZT to lymphatic tissue and maintain effective AZT concentration in lymphatic tissue is of importance.…”
Section: Although Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…This discovery suggested that targeting of AIDS drug to lymphatic tissue and sustaining a high therapeutic drug concentration in lymphatic tissue may improve therapeutic benefits, especially in the latent period. However, it has been reported that azidothymidine (AZT) administration during an early clinical latent stage did not provide benefits to HIV -infected patients, 3 since AZT fails to be targeted and sustained in lymphatic tissue, 4 • 5 and has serious side effects and drug resistance. 6 Therefore, preparation of an AZT prodrug which may deliver AZT to lymphatic tissue and maintain effective AZT concentration in lymphatic tissue is of importance.…”
Section: Although Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…3′‐Azido‐3′‐deoxythymidine ( 1 , AZT, Zidovudine, Retrovir) was the first chemical agent approved by the Food and Drug Administration (FDA) for the treatment of AIDS 1. However, there were some major problems in its clinical application, such as bone marrow toxicity and suppression, low therapeutic index and low localization in the brain 2,3. In order to improve the therapeutic potential of AZT, a number of prodrugs have been synthesized to deliver AZT in vivo 4.…”
mentioning
confidence: 99%
“…Manouilov et al demonstrated that lipophilicity is a key factor for retention of antiretroviral drugs in lymph nodes [14]. The 6-Cl-ddG is a highly lipophilic antiretroviral prodrug [22].…”
Section: Discussionmentioning
confidence: 99%
“…Manouilov et al demonstrated that lipophilicity is a key element in the targeting of antiretroviral drug to lymph nodes [14]. They showed that, in mice, administrated AZT rapidly disappears from lymph nodes serologically negative for B virus, simian T-cell leukemia virus type I and simian type D retrovirus.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation